Sonodynamic therapy of hypoxic tumours - Beguin, E (2018)
Improvements in cancer therapies have enabled a steady increase in the five-year survival rates of patients with most tumour types. Yet, some highly aggressive tumours still present resistance to conventional cancer therapies. One of the explanations for this has been ascribed to the low levels of oxygen seen in the tumours’ vicinity. In this manuscript, the development of sonodynamic therapy to enable the treatment of hypoxic pancreatic tumours is presented. With this technique, low intensity ultrasound is used to activate oxygen-loaded microbubbles in order to provide oxygen in hypoxic lesions and enable their treatment using an ultrasound-responsive drug: Rose Bengal. An investigation on mechanisms demonstrated that light generated from collapsing microbubbles allows the activation of Rose Bengal during ultrasound exposure. Several acoustic parameters were also evaluated to understand their impact on treatment. To enhance the delivery of oxygen and the sonodynamic effect, magnetic targeting of microbubbles was enabled by incorporating iron oxide nanoparticles within their coating. Thus, an external magnetic field focused at the tumour can be used to target this therapy. A structural analysis of microbubbles as drug and oxygen carrier was then undertaken to optimise the system’s stability and performance. An evaluation of this method in preclinical in vivo experiments demonstrated that magnetically targeted sonodynamic therapy with oxygen microbubbles and Rose Bengal enabled a decrease in size of hypoxic pancreatic tumours in a murine model. Therefore, this thesis presents promising results for the treatment of hypoxic tumours using sonodynamic therapy, as well as key mechanistic and parametric results to enable the further optimisation of this method for clinical use.